2021
DOI: 10.1039/d0tc05093h
|View full text |Cite
|
Sign up to set email alerts
|

From AgGaS2to AgHgPS4: vacancy defects and highly distorted HgS4tetrahedra double-induced remarkable second-harmonic generation response

Abstract: Great enhancement of the second harmonic generation response is achieved in AgHgPS4 by introducing vacancy defects and highly distorted HgS4 tetrahedra using AgGaS2 as the template.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 62 publications
5
31
0
Order By: Relevance
“…In terms of the way of anion accumulation, the 3D DL structure of Cu 5 Zn 0.5 P 2 S 8 can be seen as an arrangement of sulfur atoms in a hexagonal close packed arrangement of sulfur layers stacked perpendicular to ab plane (Figure d). As given in Table S3, the M(1), Cu(2) and P atoms are tetrahedral coordination, and the bond lengths of M(1)–S, Cu(2)–S, and P–S lie in the ranges of 2.285(2)–2.312(2) Å, 2.303(3)–2.368(3) Å, and 2.055(4)–2.071(3) Å, respectively, which are similar to the situation reported in other DL chalcophosphates. …”
supporting
confidence: 81%
See 2 more Smart Citations
“…In terms of the way of anion accumulation, the 3D DL structure of Cu 5 Zn 0.5 P 2 S 8 can be seen as an arrangement of sulfur atoms in a hexagonal close packed arrangement of sulfur layers stacked perpendicular to ab plane (Figure d). As given in Table S3, the M(1), Cu(2) and P atoms are tetrahedral coordination, and the bond lengths of M(1)–S, Cu(2)–S, and P–S lie in the ranges of 2.285(2)–2.312(2) Å, 2.303(3)–2.368(3) Å, and 2.055(4)–2.071(3) Å, respectively, which are similar to the situation reported in other DL chalcophosphates. …”
supporting
confidence: 81%
“…There are some remarkable examples such as AgZnPS 4 (E g = 2.76 eV; d ij = 1.8AgGaS 2 ), 15 CuZnPS 4 (E g = 3.0 eV; d ij = 3AgGaS 2 ), 16 HgCuPS 4 (E g = 2.03 eV; d ij = 6.5AgGaS 2 ), 17 and HgAgPS 4 (E g = 2.63 eV; d ij = 5.1AgGaS 2 ). 18 Compared with the quaternary system, ternary thiophosphates with DL structure are rarely reported, and the known examples only existed in InPS 4 (E g = 3.12 eV; d 36 = 14 pm/V), 19 Zn 3 P 2 S 8 (E g = 3.12 eV; d ij = 2.6AgGaS 2 ), 20 and Sn 2 P 2 S 6 (E g = 2.34 eV; d 11 = 12 pm/ V). 21,22 In the meantime, ternary Cu 3 PS 4 came into our sights, and it was thought to perform well by theoretical studies (d 33 = 21 pm/V), but no relevant experimental reports of its NLO performance were published.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is found that the structure of (Na 3 Rb)Hg 2 Ge 2 S 8 is composed of the typical [HgS 4 ] tetrahedron with d (Hg–S) = 2.460(13)–2.641(13) Å and the [GeS 4 ] tetrahedron with d (Ge–S) = 2.192(15)–2.237(14) Å, which are in accordance with those of related compounds. 55,56 Interestingly, each [HgS 4 ] tetrahedron is coordinated with four [GeS 4 ] tetrahedra, and each [GeS 4 ] tetrahedron is also coordinated with four [HgS 4 ] tetrahedra, which are alternately connected via corner-sharing forming a three-dimensional (3D) covalent framework structure [HgGeS 4 ] 2− , as shown in Fig. S2 (ESI†).…”
Section: Resultsmentioning
confidence: 99%
“…Among the various IR NLO‐active anionic groups, Hg‐based BBUs are very competitive due to several advantages: 1) Hg 2+ cation possesses highly polarizable and deformable electron cloud, which would significantly increase the second harmonic generation (SHG) effect and birefringence; [ 12 ] 2) multiple coordination modes of Hg exist including linear, trigonal‐planar, and tetrahedral geometries, which provide opportunities to construct novel structures. Many Hg‐based IR NLO crystals have been discovered recently in both halides and chalcogenides systems with strong SHG responses and wide bandgaps ( E g ), such as Na 2 Hg 3 Ge 2 S 8 (2.2 × AGS; 2.68 eV), [ 13 ] BaHgSe 2 (1.5 × AGS; 1.56 eV), [ 14 ] SrHgGeSe 4 (4.8 × AGS; 2.42 eV), [ 15 ] CuHgPS 4 (6.5 × AGS; 2.03 eV), [ 16 ] AgHgPS 4 (5.06 × AGS, 2.63 eV), [ 17 ] Cs 2 HgI 2 Cl 2 (1 × KDP; 3.15 eV), [ 18 ] and RbHgI 3 (7 × KDP; 2.56 eV). [ 19 ] Thereby, mixed‐anion [HgQ m X n ] BBUs are expected to exist and perform well.…”
Section: Introductionmentioning
confidence: 99%